PENGARUH CORPORATE GOVERNANCETERHADAPPENGUNGKAPANSUKARELA: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (STIE Rajawali Purworejo, 2018)
This study aims to examine the effect of Good Corporate Governance on Voluntary Disclosure. The company's voluntary disclosure uses indicators consisting of 3 categories: Strategic Information, Non Financial Information and Financial Information. The Corpo rate Governance in this study uses 5 indicators,namely the proportion of independent board of commissioners, the proportion of independent audit committee, managerial ownership, institutional ownership, and size of public accounting firm, and company size as control variable. By proportional random sampling method, 70 annual reports of Indonesian manufacturing companies were selected. Analytical tool to test the hypothesis is multiple regression analysis using SPSS 16.0 program. The results of this study indicate that the proportion of independent board of commissioners, the proportion of independent audit committees, managerial ownership, institutional ownership, and the size of public accounting firms simultaneously affect voluntary disclosure. While in part, the results show that the portion of the independent audit committee and the size of the public accounting firm have a significant positive effect on voluntary disclosure. Institutional ownership negatively affects voluntary disclosure. While the prop ortion of independent board of commissioners, managerial ownership and firm size has no significant effect on voluntary disclosure in the annual report.